Prescription ethics in a low-middle income country: Thematic analysis of research from Pakistan - Tashfeen Ahmad; Ceemal Khan; Kausar Saeed Khan (Journal of the Pakistan Medical Association, 2024)
The ethics of physician prescriptions is a matter of globalconcern. While commonalities exist in reasons forunethical prescribing practices such as physicianincentivization by pharmaceutical companies, theunderlying social determinants may be different acrosscountries and socioeconomic strata. This scoping reviewhas collected themes from publications aroundprescription ethics from Pakistan. Four major themeswere identified: 1) Impact – including physical andfinancial harm to patients, deficit in trust anddevelopment of antibiotic resistance, 2) Causes –including personal financial needs, peer pressure,inadequacy of education in ethics and professionalism,lack of evidence for policy-making, and weak regulatoryframework, 3) Type – includes unethical practices likeexcessive, inappropriate/unnecessary, expensive, nonevidence-based, and off-label prescriptions, andprescription of controlled drugs to addicts, and 4)Solution – proposed strategies to curb unethicalprescribing practices included education of communityand undergraduates, trainees and practicing physicians,improvement in policies/laws on drugdispensation/prescriptions, their enforcement andaccountability, as well as making health care accessible. Insummary, this review identifies various socialdeterminants of prescription ethics in the context ofPakistan, a low-middle income country, and highlightslocally applicable measures to prevent unethicalprescribing practices. Keywords: Ethics, prescriptions, incentive-linked,inducement, enticement, incentivization, Pakistan